Pelatihan Dan Pedampingan Pembuatan Pupuk Kompos BumDes Manik Mandiri Desa Gunungmanik - Trisolvena, Muhammad Nana; Johan; Bastian, Norman; Nurdianti, Dewi; Perwitasari, Fitri Dian; Utami, Arie Susetio; Kunaedi, Aan (Jurnal SOLMA, 2023)
Background: BUMDes is a rural economic empowerment platform that cultivates various village potentials. Under the coordination of BUMDes, it is expected that all economic empowerment will be carried out following the needs of rural communities to increase the economy and income of the community and village. This mentoring activity aims to enable farmers to utilize cow dung in compost as organic fertilizer for agricultural commodity crops in Gunungmanik Village. Method: The exercises provided are counseling and assistance in making compost. The target of this activity is members of BumDes Manik Mandiri Desa Gunungmanik. Results: The activities carried out are as follows: 1) Giving presentations and discussing with the participants, 2) Conduct field practice of making compost. The action will be held on Friday and Saturday, September 25-26, 2021, at 10.00 - 16.00 WIB. Conclusion: The benefits of this PPM activity are that participants know and understand how to make and use compost and make plans to make compost as a BUMDES business unit.